Ageing, funded pensions and the Dutch economy - Ary Lans Bovenberg; Thijs Knaap (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper attempts to paint a coherent picture of the effects of ageing on a small, open, economy with large pension funds in different institutional settings. Quantitative scenarios are projected with an applied computable general equilibrium model with institutional details. We find that ageing leads to a tighter labor market, increasing costs for both pension funds and the government, and leaving the economy vulnerable to financial and further demographic shocks. We show that defined benefit pension arrangements can be destabilizing, but less so if an average-wage variable-indexation contract is chosen. Government can help by adopting a policy of tax smoothing, but the single most important determinant of the net burden of ageing is the eventual size of the increase in labor market participation of older workers. The intergenerational welfare effects of demographic shocks and changes in international interest rates are sizable and should be an integral part of the assessment of different policy instruments.
Keywords: E17; H30; J18; 330; ageing; funded pensions; applied general equilibrium models; the Netherlands; Alternde Bevölkerung; Pensionsfonds; Gesetzliche Rentenversicherung; Kapitaldeckungsverfahren; Bevölkerungsökonomie; Allgemeines Gleichgewicht; Overlapping Generations; Wohlfahrtseffekt; Theorie; Niederlande